Prediction of Drying Characteristics of Pomegranate Arils - Doymaz, Ibrahim (SPRINGER, 2012)
The thin-layer drying characteristics of pomegranate arils were investigated at the temperature of 55, 65 and 75A degrees C, and the thin-layer drying models were used to fit the drying data. The increase in drying air temperature resulted in a decrease in drying time. Five different thin-layer drying models were used to predict the drying characteristics. The Midilli et al. model showed a better fit to experimental drying data as compared to other models. Effective moisture diffusivities were calculated based on the diffusion equation for a spherical shape using Fick's second law, and varied from 9.373 x 10(-11) to 3.429 x 10(-10) m(2)/s over the temperature range. Moisture diffusivity values increased as air temperature was increased. The dependence of moisture diffusivity on temperature was described by an Arrhenius-type equation. The activation energies of control and pre-treated samples were determined to be 49.7 and 40.1 kJ/mol, respectively.
Keywords: Activation energy; Effective moisture diffusivity; Pre-treatment solution; Pomegranate arils; Thin-layer drying; MOISTURE DIFFUSIVITY; KINETICS; PRETREATMENTS; QUALITY; TEMPERATURE; COLOR; GRAPE; Food Science & Technology